2013
DOI: 10.4000/norois.4729
|View full text |Cite
|
Sign up to set email alerts
|

Les épis de la Loire armoricaine, un héritage à la patrimonialité incertaine

Abstract: La Loire armoricaine (entre Les Ponts-de-Cé et Nantes) est comprise entre deux pôles de patrimonialisation intense : l'estuaire à l'aval et le Val de Loire inscrit au patrimoine mondial de l'Unesco. Cette section du l euve est profondément marquée par la crise morpho-sédimentaire et écologique liée à l'abaissement de la ligne d'eau à l'étiage. Cette crise révèle le forçage de la dynamique l uviale du l euve, dont l'incision du lit engagée dès la i n du xix e siècle, et a été amplii ée par l'extraction sablière… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
2
0
5
Order By: Relevance
“…until the 1980s. As for PAHs (Bertrand et al, 2015), the Ondaine-Furan corridor was likely the main contributor to the upper Loire PCB contamination. In the middle Loire stretch, several urban and industrial zones are found (Nevers, Orléans, Tours), although the low quantity of available data does not allow us to evaluate PCB pollution trends in those areas.…”
Section: Spatio-temporal Distribution Of the Pcb Contamination And Immentioning
confidence: 99%
“…until the 1980s. As for PAHs (Bertrand et al, 2015), the Ondaine-Furan corridor was likely the main contributor to the upper Loire PCB contamination. In the middle Loire stretch, several urban and industrial zones are found (Nevers, Orléans, Tours), although the low quantity of available data does not allow us to evaluate PCB pollution trends in those areas.…”
Section: Spatio-temporal Distribution Of the Pcb Contamination And Immentioning
confidence: 99%
“…Two types of river engineering associated with distinct time period can generally be distinguished: most infrastructures related to flood protection and facilitation of navigation (embankments, dikes, groynes, locks) were implemented in the 18 th and 19 th century, while infrastructures for hydroelectricity production (reservoirs, run-of-river dams and flow diversions) were mainly built during the 20 th century (Habersack and Piegay, 2007). Construction periods may vary depending on regional or national development disparities: the first major engineering works in the Netherlands were carried out on the Rhine River in the early 1700s (Yossef, 2002); on the Oder River in Poland, weirs and groynes were built on a large scale from 1741 to 1896 (Buczyńska et al, 2018); in Hungary, flood-control dykes and groynes were built on the Middle Danube between 1871 and 1914 (Gupta, 2008) and groynes on the Loire River in France were built in the beginning of the 20 th century (Barraud et al, 2013). Regarding hydropower, the first European plant was built in 1893 in Serbia (Marković, 2012), and the number of facilities then grew exponentially over Western Europe during the next century.…”
Section: Europe: a Comparison In The Anthropocene Periodmentioning
confidence: 99%
“…Des travaux récents ont déjà investi ce secteur de la Loire armoricaine et des problématiques proches 1 . Les recherches menées sur les épis de Loire construits au début du XX e siècle ont montré que ces derniers n'ont pas fait l'objet d'un fort processus de patrimonialisation, mais qu'ils ont néanmoins constitué un support d'appropriation de la part de la population locale (Barraud et al, 2013 ;Davodeau et al, 2013). Dans notre article, nous ne nous attachons pas à ces ouvrages anciens liés à la navigation fluviale, mais à des aménagements beaucoup plus récents.…”
unclassified
“…Un des exemples qui est utilisé à cet égard est celui de la suppression des épis en 2009 sur le lit mineur de la Loire entre Bouchemaine et Chalonnes-sur-Loire et ses effets sur l'efficacité du piégeage des sédiments (entretiens de terrain ; Barraud et al, 2013) ou encore les craintes soulevées par certains habitants du village de Bellevue quant aux dangers d'inondations liés au relèvement de la ligne d'eau.…”
unclassified
See 1 more Smart Citation